Word Cup and Olympic Games analysis of 3m and 10m diving - Bratta, C.; Demarie, S.; Cortis, C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Sex differences in world ranked performance has been suggested to follow a diminishing trend that could lead women to reach men`s results, particularly in longer events (reference 1). The same trend has not been consistently reported either for short and middle-distance events, or for technical disciplines (references 2,3). Performance trend analysis could be useful to plan athlete`s careers and to discriminate between men and women developmental patterns. The aim of this study was to analyze the trend of the differences in performances between male (M) and female (F) athletes in Olympic Games (OL) and World Cup (WC) from Sydney 2000 to Tokyo 2020 in 3m springboard and 10 m platform diving.